The Developing of PBL Oriented E-Magazine to Improve Critical Thinking Skills and Caring Attitudes Laboratory Work Safety - Trisna, Mila; Iswari, Retno Sri; Susanti, R. (Journal of Innovative Science Education, 2022)
This research aims to test the validity and effectiveness of Problem Based Learning (PBL) oriented e-magazine teaching materials in improving critical thinking skills and caring attitude towards laboratory work safety. This research is a Research and Development (R&D) research that uses the ADDIE model by applying a pretest-posttest control group design. The subjects in this study were 51 students of class X MIA SMA N 7 Jambi City. Research instruments in the form of expert validation questionnaires, questionnaires on the readability of teaching materials, critical thinking skills test questions and attitudes about laboratory safety. The data analysis of the expert, practitioner, legibility and practicality validation questionnaire data showed that the validity of the e-magazine was considered very valid. Effective teaching materials improve critical thinking skills seen from the posttest average of the experimental class is 80.1 and the control class is 71.3. The average N-gain of the experimental class is 0.59 (medium) and in the control class is 0.33 (medium). Effective teaching materials increase the attitude of caring for safety as seen from the posttest average of the experimental class of 79.6 and the control class of 74.7. The average N-gain of the experimental class is 0.55 (medium) and in the control class is 0.42 (medium). Based on the research results, PBL-oriented e-magazines are valid for use in learning and are effective in improving critical thinking skills and caring attitude towards laboratory safety.